The Role of Data Warehouse in Enhancing Information and Communication Technology - Alsqour, Moh'd; Owoc, Mieczysław L (Rola hurtowni danych jako elementu wzbogacającego technologie informacyjne i komunikacyjne, 2010)
Information is one of the most valuable resources available for improving public and private administration’s system for achieving social development. Recent advances in information technology (IT) form the basis of an entirely new era in delivering of services. This paper aims at pushing back the frontiers of information society (IS), deepening its role of enhancing human life in this era, and ascertaining the importance of data warehouse (DW) in information and communication technology (ICT) in order that guarantee of data and information’s quality can be reached. These latest technological developments argue a change in national policy. Therefore, the authors recommend maximizing the use of these technologies to facilitate information processing as a public and private sectors objective.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 11-19
Keywords: information technology; information society; data warehouse